2021
DOI: 10.3390/en14185839
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Environmental Degradation, Climate Change, and the European Green Deal Tools on Life Satisfaction

Abstract: Environmental issues, sustainability, and climate change have become the targets of many policies from international and governmental organizations including the EU’s European Green Deal action plan. This plan provides tools to address them—which include support for the circular economy, implementation of energy and environmental taxes, and investment in environmental protection—with the aim of favoring the well-being of EU citizens. In this context, this study analyses the impact of several parameters (enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Therefore, its decrease increases the probability that more than 25% of a country's citizens have satisfaction levels equal to or below 5. In line with the study conducted by [58], and in the opposite direction to the results of this work, are the studies by [59][60][61].…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, its decrease increases the probability that more than 25% of a country's citizens have satisfaction levels equal to or below 5. In line with the study conducted by [58], and in the opposite direction to the results of this work, are the studies by [59][60][61].…”
Section: Discussionsupporting
confidence: 86%
“…However, this study aims to highlight the fundamental objections to the EGD by considering the market's entrepreneurial and competitive aspects [90]. A systematic evaluation of the specialized literature was made to gather information regarding the issue [91]. The study's findings demonstrated that, despite the free market, the EGD prioritizes the environment and has an impact on entrepreneurial activity [92].…”
Section: Literaturementioning
confidence: 99%
“…In rural areas, residents' satisfaction with rural ecological environment governance is based on certain environmental information and comes from all aspects of production and life. Environmental issues and environmental disclosures affect residents' life satisfaction or subjective well-being [30,31]. For example, air quality and rural greening all play a significant part in the living environment of residents; that is, clean and fresh air quality, good rural greening and maintenance will directly affect rural residents' satisfaction with the improvement of the living environment [32].…”
Section: Environmental Governance Satisfactionmentioning
confidence: 99%